A web-based preventive intervention program for bipolar disorder: Outcome of a 12-months randomized controlled trial - Barnes, Caryl W.; Hadzi-Pavlovic, Dusan; Wilhelm, Kay; Mitchell, Philip B. (Journal of affective disorders, 2015)
The Internet is used to deliver information on many psychiatric disorders such as bipolar disorder. This paper reports on the results of a 12-months randomised controlled trial, which examined the efficacy of an Internet-based preventive program for bipolar disorder, adjunctive to usual pharmacological management. Participants were recruited by completing an online screening questionnaire accessed through the Black Dog Institute and Sentiens websites based in Australia. The treatment was predominantly psycho-educational with cognitive behavioral therapy optional elements. The attention control treatment comprised directing subjects to a variety of websites focused on ‘healthy living’. Time to recurrence was determined using Kaplan–Meier survival analysis. The main outcome measures were recurrence as defined by: (i) depressive and/or hypomanic symptomatology and functional capacity (using Beck Depression Inventory, Internal State Scale and Sheehan Disability Scale) and (ii) hospitalization. Two-hundred-and-thirty-three subjects were randomized to the active or control treatment groups. There were no significant differences between the active and control treatment groups on any of the definitions of recurrence. Reliance on an online self-report tool to confirm diagnosis and hospitalization rates may have potentially allowed for inclusion of individuals with other diagnoses such as borderline personality disorder. The ‘attention control’ treatment may have included more ‘active’ components than intended. This is the first report examining the efficacy of a randomized controlled web-based psychological intervention in a large sample of subjects with bipolar disorder. The potential reasons for failing to demonstrate a significant difference compared to the active control are discussed.